2017
DOI: 10.1210/jc.2017-01850
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Levothyroxine on Pregnant Women With Subclinical Hypothyroidism, Negative for Thyroid Peroxidase Antibodies

Abstract: Despite no beneficial effect of LT4 therapy in reducing preterm delivery in SCH-TPOAb- women with a TSH cut point of 2.5 to 4 mIU/L, LT4 could precisely decrease this complication using the newly recommended cutoff ≥4.0 mIU/L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
89
3
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 29 publications
2
89
3
6
Order By: Relevance
“…12 A subsequent study from the same group failed to show any levothyroxine treatment difference in preterm delivery in anti-TPO negative women when a TSH cut-off of 2.5 mU/L was applied, but there was a reduction using a TSH cut-off of 4.0 mU/L. 13 A retrospective analysis of a large US administrative claims database showed that pregnant women with subclinical hypothyroidism treated with levothyroxine had reduced pregnancy loss compared to untreated women, but only in those with pre-treatment TSH concentration of 4.1-10 mU/L. 14 Limitations of this study included the retrospective observational design, potential for misclassification, selection bias and other confounders. A recent systematic review involving 3995 pregnant women supported an association between subclinical hypothyroidism and adverse maternal and neonatal outcomes; however, this association may not be causal and may be overestimated by publication bias.…”
Section: Subclinical Hypothyroidism In Pregnancymentioning
confidence: 98%
See 1 more Smart Citation
“…12 A subsequent study from the same group failed to show any levothyroxine treatment difference in preterm delivery in anti-TPO negative women when a TSH cut-off of 2.5 mU/L was applied, but there was a reduction using a TSH cut-off of 4.0 mU/L. 13 A retrospective analysis of a large US administrative claims database showed that pregnant women with subclinical hypothyroidism treated with levothyroxine had reduced pregnancy loss compared to untreated women, but only in those with pre-treatment TSH concentration of 4.1-10 mU/L. 14 Limitations of this study included the retrospective observational design, potential for misclassification, selection bias and other confounders. A recent systematic review involving 3995 pregnant women supported an association between subclinical hypothyroidism and adverse maternal and neonatal outcomes; however, this association may not be causal and may be overestimated by publication bias.…”
Section: Subclinical Hypothyroidism In Pregnancymentioning
confidence: 98%
“…A further study of anti‐TPO positive women with TSH >2.5 mU/L treated with levothyroxine before 14 weeks’ gestation also found a reduced risk of pre‐term delivery, but mainly in those with TSH >4.0 mU/L . A subsequent study from the same group failed to show any levothyroxine treatment difference in pre‐term delivery in anti‐TPO negative women when a TSH cut‐off of 2.5 mU/L was applied, but there was a reduction using a TSH cut‐off of 4.0 mU/L . A retrospective analysis of a large US administrative claims database showed that pregnant women with subclinical hypothyroidism treated with levothyroxine had reduced pregnancy loss compared to untreated women, but only in those with pre‐treatment TSH concentration of 4.1–10 mU/L .…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al reported an overall reduction in pregnancy complication rate in women treated in the first trimester, but not in those treated in the second trimester (22). Similarly, the randomized controlled trial by Nazarpour et al initiated treatment soon after the first prenatal visit, and found a reduction in the rate of preterm delivery in treated women (23).…”
Section: C) Treatment Of Subclinical Hypothyroidism (Question 37)mentioning
confidence: 99%
“…and (Recommendation 29) LT4 therapy is recommended for TPOAb-positive women with elevated TSH and TPOAb-negative women with a TSH >10.0 mIU/L; LT4 therapy may be considered for TPOAb-positive women with TSH >2.5 mIU/L or TPOAb-negative women with elevated TSH; LT4 therapy is not recommended in TPOAb-negative women with normal TSH Five studies published since the 2017 ATA Guidelines addressed the treatment of subclinical hypothyroidism in pregnancy (22)(23)(24)(25)(26). Two studies reported a decrease in negative perinatal outcomes in women who were treated (22,23). In a prospective study of 93 women with subclinical hypothyroidism, defined as TSH above 2.5 mIU/L in the first trimester or above 3.0 mIU/L in the second trimester, Zhao et al 22 (23).…”
Section: C) Treatment Of Subclinical Hypothyroidism (Question 37)mentioning
confidence: 99%
See 1 more Smart Citation